1995
DOI: 10.1017/s0021859600072956
|View full text |Cite
|
Sign up to set email alerts
|

Digestion, rumen fermentation and chewing behaviour of red deer fed fresh chicory and perennial ryegrass

Abstract: Pure chicory {Cichorium intybus) and perennial ryegrass {Lolium perenne) forages were cut and fed fresh at Palmerston North, New Zealand, during March 1993 to castrated male red deer kept indoors in metabolism crates. Chicory contained lower levels of dry matter, higher levels of ash, and had a higher ratio of readily fermentable: structural carbohydrate than perennial ryegrass. Apparent digestibility of organic matter was highest for chicory (0-81 v. 0-72), but cellulose apparent digestibility was highest for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
5
27
0
Order By: Relevance
“…The DM content of the chicory/ryegrass swards were lower than the ryegrass treatment, reflecting other research findings for a low DM content of chicory in comparison to ryegrass [9], [43]and that increasing proportions of chicory within ryegrass swards reduced the DM content of the harvested forage [44]. Factors affecting voluntary intake in ruminants are complex in nature but it is influenced by forage DM content [45] and it was possible that the low DM of chicory could have reduced voluntary intake, and thus the performance, of the beef steers in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…The DM content of the chicory/ryegrass swards were lower than the ryegrass treatment, reflecting other research findings for a low DM content of chicory in comparison to ryegrass [9], [43]and that increasing proportions of chicory within ryegrass swards reduced the DM content of the harvested forage [44]. Factors affecting voluntary intake in ruminants are complex in nature but it is influenced by forage DM content [45] and it was possible that the low DM of chicory could have reduced voluntary intake, and thus the performance, of the beef steers in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…Deer grazing chicory spend slightly less time eating and significantly less time ruminating than those grazing pasture (Kusmartono et al 1996a). Hoskin et al (1995) showed that deer fed freshly-cut pure chicory indoors spent a similar time eating (361 v 379 min/24h) but markedly less time ruminating (33 v 270 min/24h) than those fed perennial ryegrass. Kusmartono et al (1996b) showed that the reduced ruminating time was associated with faster rumen particle breakdown and faster disappearance of DM from the rumen in deer fed chicory, thus explaining the potential for greater autumn VFI in deer grazing this species.…”
Section: Discussionmentioning
confidence: 98%
“…It has been found that rumen microfloras adapted to digest high-quality diets contain larger numbers of protozoa (Giesecke and Van Gylswyk 1975;Hoskin et al 1995) and large bacteria (Giesecke and Van Gylswyk 1975) than non-adapted rumen microfloras. Nevertheless, Baker and Dijkstra (1999) pointed out the difficulty of estimating variations in the rumen flora; for example, some components have symbiotic relationships and others are associated with the fluid phase of the rumen content, and are therefore easily quantified, but others are associated with the surface of the solid phase of the rumen content or even fixed to the rumen mucosa.…”
Section: Interaction Between Rumen-microflora Adaptation and Substratesmentioning
confidence: 99%